Effect of level of Interleukin 1 beta (Il-1B) and Luteinizing hormone (LH) impacts on the size of the ovarian follicles of local cows - Al-Janabi , Retaj Aqeel; Aldulaimi, Makki Khalaf (Journal of Kerbala for Agricultural Sciences, 2023)
This study was conducted in the laboratories of the Department of Animal Production Techniques at the Technical College in Mussaib (TCM) from September 2021 to January 2022 to study the relationship between Interleukin 1 beta (il-1B) and Luteinizing hormone (LH) with ovarian follicle size on local cows. 150 reproductive systems were collected from non-pregnant local cows, which slaughtered in the abattoirs of Babylon Province and were transported to the laboratory within two hours. Ovaries were removed (300 ovaries) and their dimensions were measured. The follicles were measured and classified into three categories. Follicular fluid was drawn from the visible follicles (2-8) on the surface of each ovary and placed in an Eppendorf tube to measure the concentration level of Interleukin 1 beta (il-1B) and Luteinizing hormone (LH) in the follicular fluid. The results showed a significant high superiority (P<0.01) of an increase in the level of interleukin-1beta over the size of large, medium and small follicles. A significant high effect (P<0.01) of increasing the level of the ovulation hormone on follicle size was observed for all small, medium and large groups. We conclude from this study that the concentrations of cytokines (interleukin-1beta) and hormones (Luteinizing hormone) are influenced by the size of the ovarian follicle.